FOREIGN EXPERIENCE OF FINANCIAL, CREDIT AND INVESTMENT SUPPORT OF SMALL BUSINESS - Skoryk Maryna Olehivna; Tkachenko Volodymyr Valentynovych; Marchenko Olha Ivanivna; Kucherenko Volodymyr; Hmyrya Viktoriia Petrivna (Scientific Journal of Pedagogy and Economics, 2020)
The article deals with the question of studying the foreign experience of financial, credit and investment support for small businesses. The forms, types and methods of budget regulation are considered as components of the state support mechanism. The sources of state support for small business are characterized. A significant analysis of foreign experience in supporting small businesses has been made. The feasibility of implementing foreign experience in financial, credit and investment support of small business in Ukraine is substantiated. Goal. To study the foreign experience of financial-credit and investment support for small business, to substantiate the feasibility of implementation of foreign experience in the implementation of the financial mechanism of development of small business in the national economy. Methods. The methodological basis of the research is general scientific and special methods of scientific knowledge. Among them are the following: methods of analysis and synthesis, induction and deduction - to reveal approaches to forms, methods and sources of state support for small business, as well as to justify the cause and effect relationships and to determine the factors that influence the development of small business in current conditions; method of comparison – during the study of foreign experience of functioning of small business and the possibilities of its use in domestic practice. Results. Some aspects of the development of small business in France are analyzed by constantly improving the skills of managerial staff of small firms and creating legislative guarantees to prevent bankruptcy. The successful experience of economic growth through the development of small business in Asian countries is analyzed, which are developing, among which: Taiwan, Singapore, Indonesia. The experience of state support of small business in India through the development of export activities of small companies, the provision of tax and customs benefits, subsidies, lower rental rates and concessional financing is considered. The effectiveness of the experience of state regulation of small business in Japan is analyzed. The experience of the United States of America and Canada, which actively provide guarantees for loans to small businesses, is examined. In Germany, in turn, the state pays more than 50% of consultations to enterprises, and also provides annual soft loans for the modernization of production. An important role is played by the preferential tax and financial system. In the Czech Republic, the state in various forms provides comprehensive support to small enterprises to partially compensate for the lack of own funds, which is especially important at the initial stages of development, provides access to financial resources for small enterprises, stimulates the creation of new jobs, and supports export-oriented and innovative small enterprises. The main form of support for small businesses in the Czech Republic is the provision of financial support in the framework of targeted state programs.